Achieving the Lisbon goal : the contribution of VET ; final report to the European Commission - Leney, Tom [Verfasser] (QCA, 2004)
"This report focuses on the contribution of vocational education and training (VET) to achieving the aims set out at the Lisbon Conference. The consortium conducting the research has prepared the report specifically for the Maastricht conference, working between April and October 2004. The report aims to provide a basis for assessing VET systems in Europe in terms of contributing to the achievement of the Lisbon goal and to stimulate policy debate at national and European level." (Excerpt, BIBB-Doku)
Keywords: I 2.2 Europa; S 2.3 Berufsbildungspolitik; G 2.3.4 Qualifikationswandel; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; Europäische Union; EU-Bildungspolitik; Bildungssystem; Attraktivität; Beziehung Bildungssystem Beschäftigungssystem; Qualifikationswandel; Durchlässigkeit im Bildungssystem; Lebenslanges Lernen; Internationaler Vergleich